Pengembangan Pariwisata Berwawasan Lingkungan Di Tawangmangu - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
ABSTRACT: The objective of this research is to explore the cultural and natural resources to change Tawangmangu Resort to be an ecotourism area. Tourism object of natural resourses research takes place in Tawangmangu region because it has become destination tourist since a long-long time ago and wher has several objects. This research is descriptive study and uses both quantitative and qualitative methods. Data was collected by using site observation technique, interviewing with key persons, and distributing quesioner. Some data analysis techniques are quantitative analysis with mathematic mode!, scoring, and making range class for the potential resources and qualitative analysis is operate by SWOT analysis.